Adaptation and validation of the Moroccan dialect version of the nomophobia questionnaire (NMP-Q): Among university students - Hicham Khabbache; Driss Ait Ali; Abdelhalim Cherqui; Abdelaziz Allioui; Zakaria Abidli; Joumana Elturk; Murat Yildirim; Nicola Luigi Bragazzi; Gabriella Nucera; Lukasz Szarpak; Amelia Rizzo; Francesco Chirico (Heliyon, 2024)
The fear of being without a mobile phone, known as nomophobia, is a new psychological issue that has arisen with the widespread use of information and communication technologies. To understand this phenomenon, more research is needed. The present study aimed to assess the factor structure of the Moroccan dialect version of the Nomophobia Questionnaire (NMP-Q) among a sample of Moroccan university students. The study included 400 students selected by convenience sampling from two universities (Fez and Rabat). First, an Exploratory Factor Analysis (EFA) was conducted using the principal component method with Varimax rotation. Then, a Confirmatory Factor Analysis (CFA), and Exploratory Structural Equation Modeling (ESEM) were carried out. The results showed that a 20-item, four-factor model was the best fit for the data collected from the sample, indicating cross-cultural validity and the robustness of the NMP-Q's structure. This suggests that the Moroccan version of the NMP-Q is useful for assessing nomophobia behavior among Moroccan university students.